Understanding inborn errors of immunity: A lens into the pathophysiology of monogenic inflammatory bowel disease - Ouahed, Jodie Deborah (Frontiers in Immunology, 2022)
Inflammatory bowel diseases (IBD) are chronic inflammatory conditions of the gastrointestinal tract, including Crohn’s disease, ulcerative colitis and inflammatory bowel disease-undefined (IBD-U). IBD are understood to be multifactorial, involving genetic, immune, microbial and environmental factors. Advances in next generation sequencing facilitated the growing identification of over 80 monogenic causes of IBD, many of which overlap with Inborn errors of immunity (IEI); Approximately a third of currently identified IEI result in gastrointestinal manifestations, many of which are inflammatory in nature, such as IBD. Indeed, the gastrointestinal tract represents an opportune system to study IEI as it consists of the largest mass of lymphoid tissue in the body and employs a thin layer of intestinal epithelial cells as the critical barrier between the intestinal lumen and the host. In this mini-review, a selection of pertinent IEI resulting in monogenic IBD is described involving disorders in the intestinal epithelial barrier, phagocytosis, T and B cell defects, as well as those impairing central and peripheral tolerance. The contribution of disrupted gut-microbiota-host interactions in disturbing intestinal homeostasis among patients with intestinal disease is also discussed. The molecular mechanisms driving pathogenesis are reviewed along with the personalized therapeutic interventions and investigational avenues this growing knowledge has enabled.